PENERAPAN KOMUNIKASI PADA PT. SANCHO MITRA SEJAHTERA - LISA .; IVANDER WIJAYA; WILI CHANDRA; IVONE .; SUTARNO . (JURNAL ILMIAH KOHESI, 2019)
In the implementation of communication also allows the emergence of obstacles. Badrudin (2013) explains these barriersincluding semantic barriers, technical barriers, biological barriers, psychological barriers, and ability barriers. In conductingthis research, the writer uses qualitative research methods. The purpose of this study is to find out clearly about the barriersto the application of communication at PT. Sancho Mitra Sejahtera, Medan. Based on the level of explanation, this type ofresearch is descriptive research. Data collection methods used were structured interviews and then analyzed through threestages of activity namely data reduction, data presentation, and drawing conclusions. The author draws researchconclusions about communication barriers at PT. Sancho Mitra Sejahtera, Medan in the marketing division there are 4types, namely: semantic barriers, technical barriers, psychological barriers, and ability barriers. Based on the research, theauthor found that In the delivery or reception of information, there has been a misunderstanding due to the use of words orsentences that are not quite right, for example between superiors and subordinates. Subordinates mistakenly respond towhat their superiors say so that they do what their superiors are asking to do. Communication problems due to poorcommunication tools usually occur with the use of memos and messengers. Subordinates experience obstacles whencommunicating with superiors because they must be more careful in talking and also more polite and reticent. Not allinterlocutors have good ability to respond to messages or information conveyed. Error responding to messages is morecommon in the use of communication in writing.